Pengaruh Pemberian Rebusan Daun Sirih Merah (Piper Crocatum) Terhadap Penyembuhan Luka Perineum pada Ibu Postpartum di Desa Tanjung Jati Kecamatan Binjai Kabupaten Langkat - Nurul Aini Siagian; Eka Sri Wahyuni; Peny Ariani; Andayani Boang Manalu (Jurnal Kesehatan Komunitas, 2020)
Nearly 90% of labor experienced perineal tears, either with or without episiotomy. The incidence of perineal tears occurred almost 90% in normal labor. Red betel leaf or Piper crocatum is known to have chemical properties that have antiseptic and antibacterial effects. The aim of this study was to assess the duration of healing of postpartum mothers' perineal wounds using red betel leaf decoction and anti-septic drugs. The research method was quasi experimental, the population of postpartum mothers with perineal wounds. The sample of the experimental group was given red betel leaf stew as much as 4-5 pieces for 7 days 18 people and the control group 18 people. Samples were taken by consecutive sampling which was conducted in the village of Tanjung Jati Kec. Binjai Kab. Langkat in April-July 2020. The results of this study were the average healing time in the control group was 5.28 Â± 0.958 with a Min-Max 3-6 days, while in the intervention group the average healing time was 3.00 Â± 1.372 with a Min-Max 2 -5. There was a significant difference (p-value = 0.001) in the length of days of healing between the control and intervention groups. The conclusion of this study is the effect of giving red betel leaf stew (piper crocatum) on the healing of perineal wounds in postpartum mothers.